2017 3rd IEEE International Conference on Cybernetics (CYBCONF) 2017
DOI: 10.1109/cybconf.2017.7985788
|View full text |Cite
|
Sign up to set email alerts
|

MICE: Multi-Layer Multi-Model Images Classifier Ensemble

Abstract: In this paper, a new type of fast deep learning (DL) network for handwriting recognition is proposed. In contrast to the existing DL networks the proposed approach has clearly interpretable structure that is entirely data-driven and free from user-or problem-specific assumptions. It is entirely parallelizable and very efficient. First, same fundamental image transformation techniques (rotation and scaling) that are used by other existing DL methods are used to improve the generalization. The commonly used desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The most important point is that the proposed ALMMo classifier is entirely data-driven and is free from unrealistic assumptions, restrictions or problem-or userspecific prior knowledge. In other studies, we also demonstrated that ALMMo classifiers are able to achieve comparable or even better classification results against the state-of-theart approaches in more complicated problems including, but not limited to, handwriting digital recognition, remote sensing image classification without the need of predefining (problemor user-specific) parameters and thresholds [40].…”
Section: B Classificationsupporting
confidence: 55%
“…The most important point is that the proposed ALMMo classifier is entirely data-driven and is free from unrealistic assumptions, restrictions or problem-or userspecific prior knowledge. In other studies, we also demonstrated that ALMMo classifiers are able to achieve comparable or even better classification results against the state-of-theart approaches in more complicated problems including, but not limited to, handwriting digital recognition, remote sensing image classification without the need of predefining (problemor user-specific) parameters and thresholds [40].…”
Section: B Classificationsupporting
confidence: 55%
“…This work can be classified as an ensemble in a strict sense where data are distributed in a number of computing nodes. In [70], an ensemble of deep learning classifiers was designed for handwriting recognition and adopted the concept of data parallerization as with [69]. The all-pair classifier in [50] can be also grouped as an ensemble approach.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by significant progress in real-time data collection and capture, the notion of EIS has gained popularity in the community because it has been shown effective in addressing lifelong learning situation and non-stationary environments. Several extensions and variations of EIS have been put forward in the literature [39], [40], [67]- [70]. An evolving version of Vector quantization was designed in [41] and is algorithmic backbone of FLEXFIS [42], which was later extended to a more robust version including rule merging in [43], generalized rules and an incremental feature weighting mechanism in [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Letter, a new approach based on the ensemble of the recently introduced deep (fuzzy) rule-based (DRB) classifiers [11], [12] is proposed for remote sensing scene classification. The DRB classifier employs a massively parallel set of 0-order fuzzy rules as a learning engine [13].…”
mentioning
confidence: 99%